Тактика планування розслідування злочинів проти моральності у сфері статевих стосунків - Малярова, В. О.; Maliarova, V. O. (Науковий вісник Дніпропетровського державного університету внутрішніх справ. - 2013. - № 4. - С. 287-293, 2013)
Здійснено аналіз тактики планування розслідування злочинів проти моральності у сфері статевих стосунків. Досліджено взаємозв’язки між плануванням та організацією розслідування злочинів.

This article examines the tactics of planning investigations into crimes against morality in sexual intercourse. The author has investigated the relationship between planning and organization of crime investigation. Activities for the investigation of criminal proceedings related to crimes against morality in sexual relations should be observed with a speed, dynamism, conspiracy, a high level of interaction with various investigative agencies and departments of internal affairs of Ukraine. Organizational actions of the investigator to investigate criminal proceedings related to crimes against morality in sexual relations with a cross-cutting nature, include: planning coordinated investigation of criminal proceedings; involvement of necessary capabilities; establish cooperation with all agencies and officials involved in the investigation; mobilization of participants investigations; management and coordination actions of the participants the investigation.

Проведен анализ тактики планирования расследования преступлений против нравственности в сфере половых отношений. Исследованы взаимосвязи между планированием и организацией расследования преступлений.
Tactics of planning investigation crimes against morality in sexual relations
Тактика планирования расследования преступлений против моральности в сфере половых отношений
Keywords: розслідування злочинів проти моральності у сфері статевих стосунків; investigation of crimes against morality in the field of sexual relations; расследование преступлений против нравственности в сфере половых отношений; кримінальне провадження; criminal proceedings; уголовное производство; планування; planning; планирование; організація; organization; организация